Data provision of PIK3CA gene diversity and recombinant plasmids preparation for control DNA in developing the trastuzumab predictive response diagnostic kit - DESRIANI DESRIANI; BUGI RATNO BUDIARTO; WIRSMA ARIF HARAHAP; M. ALI WARISMAN; AUDREY VANIA CLARISSA OMPUSUNGGU; DINA ATHARIAH; FARIDA MIRNAWATI; IDA YUSSRIYANI; FUAD ALAHWANI; AHMAD RIZQI KURNIAWAN (Biodiversitas Journal of Biological Diversity, 2016)
Desriani, Budiarto BR, Harahap WA, Warisman MA,Ompusunggu AVC, Athariah D, Mirnawati F, Sriyani IY, Alahwani F, Kurniawan AR. 2016. Data provision of PIK3CA gene diversity and recombinant plasmids preparation for control DNA in developing the trastuzumab predictive response diagnostic kit. Biodiversitas 17: 647-652. HER-2 overexpression is well known as a poor prognostic factor for breast cancer patients. Targeted therapy can be carried out using monoclonal antibody named trastuzumab. Some reports have higlighted the core problem of HER2 positive-breast cancer resitance on trastuzumab due to incorrect in selecting HER2 status patient who will reciept the drug and the emergence of PIK3CA mutations especially in exon 9 and 20 which is the downstream of HER-2 pathway. In this study, data provision of PIK3CA gene and preparation of plasmid to support developing the trastuzumab predictive response diagnostic kits will be reported. Based on direct DNA sequencing result, two samples of 68 breast cancer patients exhibited mutation at exon 20 H1047R, while another three samples showed silent mutation (T1025T) at the same exon. On the other hand, careful strategy should be considered for exon 9 analysis, since we found that almost 68 samples sequenced none of them were exon 9 positive (pesudogene). Two prepared plasmids, pGEMT-easy PIK3CA exon 9 and 20 will be applied as control PIK3CA gene for qPCR SYBR green I-based PIK3CA genotyping, while pGEMT easy HER-2 will be applied as a reference gene for scoring HER-2 status. The standard curve equation of plasmid-cloned HER2 gene amplification was Y=-3,0472x + 46,465, R2= 0,99 with qPCR efficiency was 115%, respectively. Inconclusion, data provision and control DNA preparation of predicted factors for breast cancer patients who positively respond to trastuzumab are very fundamental important aspects for the development of trastuzumab response diagnostic kit which is based on Indonesian population genetics profile.